2006
DOI: 10.1111/j.1469-1809.2006.00312.x
|View full text |Cite
|
Sign up to set email alerts
|

Interrelationship and Familiality of Dyslexia Related Quantitative Measures

Abstract: SummaryDyslexia is a complex gene-environment disorder with poorly understood etiology that affects about 5% of school-age children. Dyslexia occurs in all languages and is associated with a high level of social and psychological morbidity for the individual and their family; approximately 40-50% have persistent disability into adulthood. The core symptoms are word reading and spelling deficits, but several other cognitive components influence the core phenotype.A broad spectrum of dyslexia related phenotypes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
48
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 63 publications
1
48
0
3
Order By: Relevance
“…Third, one limitation of this study is that we have not included measures that cover the whole spectrum of dyslexia-related traits. 38,47 Previous association studies have reported an association between some of the herein reported genes and phonological processing, orthographic awareness, auditory memory, and rapid naming. 38 The missing analysis of relevant subtypes, quantitative measures, or the severity of dyslexia could be a further factor for the lack of association in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Third, one limitation of this study is that we have not included measures that cover the whole spectrum of dyslexia-related traits. 38,47 Previous association studies have reported an association between some of the herein reported genes and phonological processing, orthographic awareness, auditory memory, and rapid naming. 38 The missing analysis of relevant subtypes, quantitative measures, or the severity of dyslexia could be a further factor for the lack of association in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The dyslexia core phenotype, however, might differ between languages. On the cognitive level, for example, various processes such as phonological decoding, phoneme awareness or orthographic processing are involved in the dyslexia core phenotype (Ramus et al 2003;Schulte-Körne et al 2007). Languages of different transparencies, such as German and English, differently apply at least some of these distinct processes.…”
mentioning
confidence: 99%
“…Our sample consisted of 244 German families with a severely affected child showing a discrepancy of at least 2 SD between expected and observed spelling score. The inclusion criteria and phenotypic measures have been previously described (Schulte-Körne et al 2007). Genotyping was performed using the iPlex-assay by Sequenom TM , and analytes were measured with a MALDI-TOF (matrix-assisted-laser desorption/ionisation time-offlight) mass spectrometry system (Bruker Daltonics).…”
mentioning
confidence: 99%
“…They found the three-marker haplotype to be paternally associated with human handedness in a set of reading-disabled sibships. We have access to a well-characterized dyslexia sample of German descent for which information on handedness is available (398 sib pairs with parents), 6 and analyzed the aforementioned 14 markers. Using the quantitative trait disequilibrium test QTDT, 7 seven markers out of 14 had nominally significant P-values < 0.05.…”
mentioning
confidence: 99%